Modern Islamic Boarding School Management in Developing Global Competitive Capabilities and Character of Santri: Manajemen Pesantren Modern Dalam Mengembangkan Kemampuan Saing Global Dan Karakter Santri - Irsyad, Sholahuddin; Widodo, Heri (Indonesian Journal of Innovation Studies, 2026)
General Background: Modern Islamic boarding schools integrate religious education with programs for students’ skills and character development. Specific Background: Pesantren eLKISI applies structured management to develop santri character, competencies, achievements, and global competitiveness. Knowledge Gap: The management practices connecting character formation and global competitiveness in modern pesantren require closer examination. Aims: This study examines how eLKISI manages its programs to develop santri character and global competitiveness. Results: The findings show that POAC management is implemented through structured planning, task organization, continuous direction, and routine evaluation. The AOD system provides 24-hour supervision, role modeling, and opportunities to develop santri interests and abilities, while international programs, competitions, language activities, and community service support global competitiveness. Novelty: The study highlights the integration of POAC management and 24-hour AOD supervision within a modern pesantren context. Implications: These practices provide a management model for developing responsible, capable, high-achieving, and globally competitive santri. Key Findings Highlights Structured POAC management supports the implementation of pesantren programs. AOD provides continuous supervision, role modeling, and character development. International programs and student achievements support global competitiveness. Keywords: Modern Islamic Boarding School, Pesantren Management, POAC Management, Santri Character, Global Competitiveness